2019
DOI: 10.1142/s0219199719500731
|View full text |Cite
|
Sign up to set email alerts
|

High-dimensional limit theorems for random vectors in ℓpn-balls. II

Abstract: In this article we prove three fundamental types of limit theorems for the q-norm of random vectors chosen at random in an ℓ n p -ball in high dimensions. We obtain a central limit theorem, a moderate deviations as well as a large deviations principle when the underlying distribution of the random vectors belongs to a general class introduced by Barthe, Guédon, Mendelson, and Naor. It includes the normalized volume and the cone probability measure as well as projections of these measures as special cases. Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Quenched LDPs for projections of various radially symmetric measures on B n p were also recently studied in [18]. We also remark that LDPs for the ℓ q norm of a random element of B n p (with q = p) were established in [17].…”
mentioning
confidence: 76%
“…Quenched LDPs for projections of various radially symmetric measures on B n p were also recently studied in [18]. We also remark that LDPs for the ℓ q norm of a random element of B n p (with q = p) were established in [17].…”
mentioning
confidence: 76%
“…A complete characterization of all distributions on B n p , which have the probabilistic representation ( 9), is hitherto unknown. Since it had been devised, authors have been using this generalized p-radial distribution in several works, for instance Kabluchko, Prochno, and Thäle [14] or Kaufmann, Sambale, and Thäle [16].…”
Section: Measures On Finite-dimensional ℓ P Spacesmentioning
confidence: 99%
“…Moreover, they provided a large deviation principle (LDP) for Z q with Z ∼ C n,p and Z ∼ U n,p . In a follow-up paper [30], the same authors showed a CLT for Z q , where the distribution of Z is taken from a wider class of p-radial distributions P n,p,W , introduced by Barthe, Guédon, Mendelson and Naor [8], consisting of mixtures of U n,p and C n,p , combined via a measure W on [0, ∞). This class contains both U n,p and C n,p , but also distributions corresponding with geometrically interesting projections (see, e.g., [30,Introduction,(iii)]).…”
Section: Introductionmentioning
confidence: 99%